2024
DOI: 10.1002/adfm.202314044
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conductive Doped Fluoride Solid Electrolytes with Solidified Ionic Liquid to Enable Reversible FeF3 Conversion Solid State Batteries

Jiulin Hu,
Meng Lei,
Chenxi Zhu
et al.

Abstract: Solid‐state lithium metal batteries based on fluorinated solid electrolytes have attracted attention due to their safety and stability advantages. However, the fluoride solid electrolytes face the problem of relatively low Li‐ion conductivity due to the lacking of suitable structural prototypes and their corresponding modulation modes. In this work, a chlorine‐doped fluoride solid electrolyte Li3AlF5.87Cl0.13 is developed with high ionic conductivity by thermal fluorination and weak chlorination of mixed ionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…On comparison, it is found that Bi 0.875 Ga 0.125 OF has the largest fluoride ion conductivity of 1.63 × 10 −3 S cm −1 at 300 K. It is also better than other focused-on solid electrolyte materials, such as La 0.9 Ba 0.1 F 2.9 (8.3 × 10 −4 S cm −1 at 430 K), 65 CsPb 0.9 K 0.1 F 2.9 (1.23 × 10 −3 S cm −1 at 300 K), 66 β-KSbF 4 (2.06 × 10 −4 S cm −1 at 330 K) 67 and Li 3 AlF 5.87 Cl 0.13 (2 × 10 −4 S cm −1 at 30 °C). 3 Therefore, Bi 0.875 Ga 0.125 OF is one kind of promising solid electrolyte for fluoride ion batteries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On comparison, it is found that Bi 0.875 Ga 0.125 OF has the largest fluoride ion conductivity of 1.63 × 10 −3 S cm −1 at 300 K. It is also better than other focused-on solid electrolyte materials, such as La 0.9 Ba 0.1 F 2.9 (8.3 × 10 −4 S cm −1 at 430 K), 65 CsPb 0.9 K 0.1 F 2.9 (1.23 × 10 −3 S cm −1 at 300 K), 66 β-KSbF 4 (2.06 × 10 −4 S cm −1 at 330 K) 67 and Li 3 AlF 5.87 Cl 0.13 (2 × 10 −4 S cm −1 at 30 °C). 3 Therefore, Bi 0.875 Ga 0.125 OF is one kind of promising solid electrolyte for fluoride ion batteries.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, with the rapid development of electric vehicles and electronic equipment, developing solid state rechargeable batteries with high density, 1–3 high voltage, 4,5 ultrahigh-rate, 6,7 safety 8,9 and long-life 10,11 has become an important strategic goal. Among various kinds of solid state rechargeable batteries, fluoride ion batteries (FIBs) 12,13 usually have multi-electron transfer characteristics, which makes them possess a high energy density of 5000 W h L −1 .…”
Section: Introductionmentioning
confidence: 99%